A new disease of wheat caused by Alternaria triticimaculans in Argentina - Perelló, Analía (1996)
Late maturity wheat plants (Triticum aestivum L) culivars Trigomax and Buck Poncho growing at the Estación Experimental Agropecuaria J Hirschhorn in Los Hornos (Provincia de Buenos Aires) were severely affected by a previously undescribed disease. The leaves initially showed necrotic, irregular brown/grey spots that progressed to general necrosis and death of the leaf. The pathogen was proposed as a new species: Alternaria triticimaculans Simmons and Perroló in 1994. Disease symptomatology and characteristics of the causal agent on potato dextrose agar are described. Eight wheat cultivars exhibited significant differences in disease severity in the field under natural infection with A triticimaculans. Don Ernesto INTA was the most resistant and Pro INTA Isla Verde the most susceptible. Five greenhouse-grown wheat cultivars were inoculated by spraying young and adult plants with conidia of A triticimaculans. Lesions similar to those observed on naturally infected plants were observed. The fungus was reisolated from all inoculated plants and Koch’s postulates were fulfilled. Adult plants were more susceptible to the pathogen than younger ones. Inoculations made on disinfected wheat seeds indicated slightly reduced seedling emergence. This is the first reported ocurrence of A triticimaculans on a cultivated plant.